1982
DOI: 10.17763/haer.52.2.n21845l740w06474
|View full text |Cite
|
Sign up to set email alerts
|

Research Report: Women in Higher Education: Trends in Enrollments and Degrees Earned

Abstract: The promise of equal opportunity in the United States implies access to education. Underlying this promise is the belief that educational achievement can be translated into occupational success. Belief in this ideal of equal opportunity and the value of education,coupled with a changing sociopolitical climate, prompted the challenges made to the educational status quo in the 1960s and 1970s. During those turbulent years women activists once again found their political voice to lobby for educational and occupat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The scarcity of longitudinal studies of the factors associated with women's entry into traditionally male-dominated professions has been noted previously (e.g., Randour, et al, 1982) and their need is abundantly clear from the preceding results. This phenomenon results from a complex interaction of the personal characteristics of women at the time they begin their undergraduate education, the characteristics of the institutions they attend, their experiences within those institutions, and their educational and employment activities following completion of their undergraduate preparation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The scarcity of longitudinal studies of the factors associated with women's entry into traditionally male-dominated professions has been noted previously (e.g., Randour, et al, 1982) and their need is abundantly clear from the preceding results. This phenomenon results from a complex interaction of the personal characteristics of women at the time they begin their undergraduate education, the characteristics of the institutions they attend, their experiences within those institutions, and their educational and employment activities following completion of their undergraduate preparation.…”
Section: Discussionmentioning
confidence: 97%
“…The percentage of women earning degrees at every level also increased substantially from 1960 to 1979 (Randour et al, 1982). More importantly, while most women were still earning degrees in female-dominated fields of study, significant shifts were seen in the proportions of women earning degrees in such traditionally male-dominated fields as agriculture, business, engineering, computer science, and the physical sciences (National Center for Education Statistics, 1981;Jacobs, 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of education, Title IX of the Education Amendments of 1972, which barred sex discrimination in federally assisted educational programs, had far-reaching effects. Other significant legislative acts that followed include formation of the Equal Employment Opportunity Commission and amendments to the act in 1972(see Ethington 1988Ferber and Lowery 1976;Randor et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Dickens and Lang (1985) find that females and minorities were primarily hired in secondary labor markets. Mainly relying on National Center for Education Statistics and the American Council on Education data, Randor et al (1982) find that women were still earning degrees in female-intensive and lower status fields. The study also found an inverse relationship between the level of degree and the percentage of women earning degrees in that respective field.…”
Section: Introductionmentioning
confidence: 99%